2014
DOI: 10.1155/2014/824630
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Live Attenuated Recombinant Pseudorabies Viruses for Use as Novel Vaccines

Abstract: Pseudorabies virus (PRV) is a double-stranded, DNA-based swine virus with a genome approximating 150 kb in size. PRV has many nonessential genes which can be replaced with genes encoding heterologous antigens but without deleterious effects on virus propagation. Recombinant PRVs expressing both native and foreign antigens are able to stimulate immune responses. In this paper, we review the current status of live attenuated recombinant PRVs and live PRV-based vector vaccines with potential for controlling viral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 72 publications
0
29
0
1
Order By: Relevance
“…There is no specific treatment for acute PrV infection. Vaccination and concurrent antibiotic therapies are recommended for alleviation of clinical signs in pigs (12,13). Therefore, development of effective antiviral agents for prevention of PrV infection is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…There is no specific treatment for acute PrV infection. Vaccination and concurrent antibiotic therapies are recommended for alleviation of clinical signs in pigs (12,13). Therefore, development of effective antiviral agents for prevention of PrV infection is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Our and other laboratories have confirmed that live attenuated pseudorabies vaccines could stimulate strong cell-mediated immune responses and high titers of neutralizing antibody against PRV and were successfully used to control PRV infection [ 37 , 38 ]. Meanwhile, live attenuated PRV have been used as a highly economical promising candidate vector for the development of bivalent vaccine from animal viruses [ 39 , 40 ]. Xu et al had determined that PRV TK − /gE − /NS1 + expressed NS1 gene of JEV (SA14-14-2) could induce JEV-specific humoral and cellular immune responses [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A somewhat new vaccine design is the live recombinant vector vaccine (RVV), a chimera of two viral genomes. There are many flavors of these, and our focus is live, self-replicating vaccines in which the vector is a harmless virus whose genome is left largely intact except for inserts of foreign genes 12 , 10 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 . Its genome is engineered to carry one or a few antigenic genes from a pathogen.…”
Section: Recombinant Vector Vaccinesmentioning
confidence: 99%